Educating for ethical leadership through web-based coaching: A feasibility study. (December 2016) - Eide, Tom; Dulmen, Sandra van; Eide, Hilde
Background: Ethical leadership is important for developing ethical healthcare practice. However, there is little research-based knowledge on how to stimulate and educate for ethical leadership. Objectives: The aim was to develop and investigate the feasibility of a 6-week web-based, ethical leadership educational programme and learn from participants' experience. Training programme and research design: A training programme was developed consisting of (1) a practice part, where the participating middle managers developed and ran an ethics project in their own departments aiming at enhancing the ethical mindfulness of the organizational culture, and (2) a web-based reflection part, including online reflections and coaching while executing the ethics project. Focus group interviews were used to explore the participants' experiences with and the feasibility of the training. Participants and research context: Nine middle managers were recruited from a part-time master's programme in leadership in Oslo, Norway. The research context was the participating leaders' work situation during the 6 weeks of training. Ethical considerations: Participation was voluntary, data anonymized and the confidentiality of the participating leaders/students and their institutions maintained. No patient or medical information was involved. Findings: Eight of the nine recruited leaders completed the programme. They evaluated the training programme as efficient and supportive, with the written, situational feedback/coaching as the most important element, enhancing reflection and motivation, counteracting a feeling of loneliness and promoting the execution of change. Discussion: The findings seem consistent with the basic assumptions behind the educational design, based partly on e-health research, feedback studies and organizational ethics methodology, partly on theories on workplace learning, reflection, recognition and motivation. Conclusion: The training programme seems feasible. It should be adjusted according to participants' proposals and tested further in a large-scale study.